Dampak Kecukupan Modal, Likuiditas, Rentabilitas, Pembiayaan Kreditur Bermasalah, Ukuran Bank terhadap Profitabilitas di Bank Perekonomian Rakyat Syariah - Anggi Amalia Putri; Ickhsanto Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the impact of Capital Adequacy, Liquidity, Profitability, Bank Size, and Troubled Creditor Financing on Profitability of Sharia People's Economy Bank. The applied research method is Purposive Sampling using secondary data taken from www.ojk.co.id and the official website of each company. The study time span covered a four-year period, from 2019 to 2022. The results showed that Bank Perekumian Rakyat Sharia showed a satisfactory level of Profitability (ROA), with Capital Adequacy reflecting Capital Adequacy Ratio (CAR) above the established minimum percentage. Profitability (BOPO), Liquidity (FDR), and Bank Size showed no significant correlation with ROA. Positive findings include a positive relationship between ROA and Capital Adequacy, while a negative relationship was found between ROA and Non-Performing Financing (NPF). Bank Size (SIZE) has no direct influence on ROA. The study emphasizes the importance of risk control, especially in managing Troubled Financing, to improve Sharia Bank profitability, while Bank Size is not the primary factor determining Profitability.